Blue lines as chromospheric diagnostics: The Al I lines at 3944 and 3961 Å - Mauas, Pablo Jacobo David (2002)
We present a simple atomic model for the synthesis of the Al I resonance lines, near the Ca II H and K lines. We study whether the computed profiles are influenced by the choice of the atomic parameters and find that, although several cross sections are not known accurately, the line profiles do not depend on them and are therefore useful as diagnostics of the atmospheric structure. We study which transitions need not to be included in the model, in order to reduce as much as possible the computing time. We compare the profiles computed for a standard model of the quiet solar atmosphere with the observations and find very good agreement. We found that the inclusion of the proper line-blanketing opacity is fundamental for an accurate calculation of the ionization balance and that irradiation by UV lines originating in the transition region does not affect the AI I emission.